Time-Variation of Dual-Class Premia - Broussard John Paul; Vaihekoski Mika (Association of Business Schools Finland, 2022)
Dual-class share structures are common in many countries. Extant literature suggests that superior voting class shares should trade at a premium over the economic (limited-voting) shares. We revisit the dual-class shares phenomenon in a low-liquidity market environment and document highly time-varying, and at times, negative dual-class premium using Finnish data from 1982 to 2018. We document two major changes in the market for the dual class shares. First, a major decline in average premium, and second, a relative decline in trading volume of the voting shares. This development took place after international investors were allowed to freely enter the Finnish market suggesting that the benefits of higher liquidity for economic shares have outweighed the voting premium creating at times a negative dual-class premium.